The role of elastic energy storage and recovery in downhill and uphill running - Snyder, K. L.; Kram, R.; Gottschall, J. S. (The Journal of Experimental Biology, 2012)
In level running, humans and other animals store and recover elastic energy during each step. What role does elastic energy play during downhill and uphill running? We measured the fluctuations of the mechanical energy of the center of mass (CoM) of 15 human participants running at 3 m s-1 on the level, downhill and uphill on a force-measuring treadmill mounted at 3, 6 and 9 deg. In level running, nearly symmetrical decreases and increases of the combined gravitational potential and kinetic (GPE+KE) energy of the CoM indicated equal possible elastic energy storage and recovery. However, asymmetrical fluctuations during hill running indicate reduced maximum possible elastic energy storage and return. We analyzed mechanical energy generation and dissipation during level and hill running by quantifying the anatomically estimated elastic energy storage (AEEE) in the arch and Achilles' tendon using peak ground reaction forces and anatomical characteristics. AEEE did not change with grade. At shallow downhill grades, the body must generate mechanical energy, though it dissipates more than it generates. At steeper downhill grades, little to no energy generation is required and only mechanical energy dissipation must occur. The downhill grade at which mechanical energy must no longer be generated occurs at approximately -9 deg, near the metabolically optimal running grade. At shallow uphill grades, mechanical energy must be generated to raise the CoM, and at steeper grades, additional energy must be generated to offset reduced elastic energy storage and return.